Cutaneous sarcoidosis at the Charlotte Maxeke Johannesburg Academic Hospital and Helen Joseph Hospital: a retrospective record review - Das, Sweta (My University, 2020)
Background: Sarcoidosis is a long-standing, granulomatous, inflammatory dermatosis which may affect multiple organ system. The aetiology of the disease is unknown. [1] Cutaneous disease occurs in 20% to 35% of patients. [2] Studies on cutaneous disease in South Africa remains limited. [15] Objectives: To demonstrate the demographic, clinical and histological characteristics of patients with biopsy proven cutaneous sarcoidosis diagnosed at Charlotte Maxeke Johannesburg Academic Hospital and Helen Joseph Hospital from 1 July 2007 to 30 June 2018.Methods: Detailed information of patients with a biopsy confirmed diagnosis of cutaneous sarcoidosis were retrospectively evaluated from histopathology reports and categorized according to gender, race, age group, clinical features and histopathology patterns found in biopsy of the skin lesions. Results: Cutaneous sarcoidosis was established in seventy-three patients. There was a marked predominance of female (71%) and black (70%) patients. The mean age at diagnosis was forty-five years. Papule, plaques and annular lesions were the most common clinical presentations. Naked sarcoidal granuloma (81%) remains the most common specific finding on histopathology. Dermal collagen sclerosis (10%) was noted as the most common nonspecific feature in this study.Conclusions: This study highlights the combined role of the dermatologist and the pathologist to recognize and diagnose cutaneous sarcoidosis simultaneously. It increases the awareness of the loopholes in our setting and enhances future possibilities of prompt diagnosis by providing minor essential details to the pathologist. The demographic, clinical features and histopathology findings in this study were mostly consistent with those published in the literature with minimal differences. Annular lesions were a common specific clinical presentation and dermal collagen sclerosis were a common nonspecific histopathology finding in this setting.
A research report submitted in fulfillment of the requirements for the degree of Master of Medicine in Dermatology to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, 2020